Rasa Bersalah Dalam Perilaku Konsumen Hijau: Tinjauan Sistematis - Olaf Ingmar; Rismono Rismono; Fitriana Puji Astuti (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2026)
Driving factors through the emotion of guilt have become an important research focus in environmentally friendly consumption patterns. There is a research gap between pro-environmental attitudes and actual behaviour in purchasing environmentally friendly products, which can be bridged by the emotion of guilt. However, studies on the psychological mechanisms of guilt in green consumption patterns still contain many inaccuracies in inducing this emotion, causing research results to become biased due to the emergence of shame, making the two emotions difficult to distinguish. Therefore, the purpose of this study is to explain the mechanism of guilt in environmentally friendly consumption patterns in a systematic manner. The research method used is a systematic literature review analysing 16 articles on the concepts of guilt and environmentally friendly consumption behaviour from 2020 to 2026. The results show that: 1. Guilt is divided into several classifications in marketing research; 2. Guilt and shame are negative emotions that can motivate actions, but they differ in their direction;3. The mechanism underlying the emergence of guilt can be divided into four major stages.